PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM GENERASI SEHAT DAN CERDAS (Studi di Kelurahan Muara Laung I, Kecamatan Laung Tuhup, Kabupaten Murung Raya) - Pahri Adi K (Journal Ilmu Sosial, Politik dan Pemerintahan, 2019)
The Healthy and Smart Generation Program is part of the National IndependentCommunity Empowerment Program which is rolled out by the goverment in orderto increase poverty and ignorance rates and encourage the creation of healthy andintelligent generations. Through this program, it is easier for the community togain access to primary and secondary education. The following discussion will bediscussed in this paper: How Community Empowerment through Healthy andSmart Generatoin programs in Muara Laung I. In order to measure the success ofthe program, the theory of empowering the Notoadmodjo Community inWaryana is used so that it can help. The research method used descriptive method.Collect and analyze information contained in verbally well written wordsembedded in it as well as community behavior. Data collection is dont throughthree steps, namely data reduction, data presentation and conclusion collection.The purpose of this study is to Analyze And Describe The Process of CommunityEmpowerment through healthy and smart generation programs is muara laung ivillage, and see what factors influence Community Empowerment Through TheHealthy And Smart Generation Program in Muara Laung I. The results of theresearch in the field of research results in the Community Empowerment programThrough the Healthy and Smart Generation Program in Muara Laung I subDistrict I have been able to finish it, but i still cannot be sure. Because it can beseen in the community, there are still people who do not know about the programand also do not know what the GSC is. Making this program still unable to servethe community the bottom.